Combination of Breast Care and Oxytocin Massage on Breast Milk Production During the Postpartum Period at the Healthy Clinic - Hanifah, Astin Nur; Septiana, Maria; Novita, Nesi; Lestari, Fika; Rejeki, Irma Sri; Wijayanti, Lumastari Ajeng (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Oxytocin massage is also a solution to overcome irregular breast milk production. This massage is performed along the spine (vertebrae) to the V and VI costae bones to stimulate the hormones prolactin and oxytocin after giving birth. The purpose of this study was to determine the role, benefits and functions of the combination of breast care and oxytocin massage on breast milk production in postpartum mothers and to facilitate breast milk production. Quasi-experimental research method, with posttest-only control design. By using consecutive sampling technique. Interventions were given from the first day to the third day postpartum, then observations were carried out. Data normality test using the Shapiro-Wilk test, data analysis using the independent t-test. The results of the study obtained a significance value with the average number of combination groups and control groups. The conclusion of this study is that the combination of breast care and oxytocin massage is effective for breast milk production in postpartum mothers. When massage is performed on the spine, it can cause a neurogenic reflex that accelerates the work of the parasympathetic nerves to convey commands to the back of the brain. As a result of the stimulatory signal, the potential action process of oxytocin is released into the systemic blood from the posterior pituitary. In the bloodstream, oxytocin is delivered to the myoepithelial cells of the alveoli and uterus so that oxytocin will stimulate these cells which cause the alveolar sacs to be compressed and the ducts to shorten and widen.